[Merry Christmas drawing from George Hasslein to William and Winifred Cody] - George Hasslein:::::::::
A self-portrait drawing of George Hasslein, with speech bubbles that say 'Merry Christmas Bill and Winnie!'; 'Had a good time at your house'; 'Bill's church is really great!'; 'Jeanne thinks you are the greatest - she wants to do a book about Bill'; and 'Happy to see you doing so well, Bill! Keep it up... soon you will be coming up here to teach!' Written Cal Poly letterhead.